(untitled) (Nashville, TN Abingdon, 1998)
Contents: v.9 : Luke, John; Includes bibliographical references, maps, charts, etc.
Donated by the Australian College of Theology. Full texts and critical notes of the New International Version and New Revised Standard Version of the Bible in parallal columns.
Keywords: Bible -- commentaries